Penerapan Strategi Example Non Example untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPS Kelas V MI Ma’arif NU 01 Sidaurip Binangun Cilacap Tahun Ajaran 2015/2016 - Maksum, Khanif (Universitas Alma Ata, 2016)
Azka Rahmatika: â€œThe Implementation of example non example strategy to improve students learning outcomes on social science subjects especially the history of hindu, buddhist and islam in Indonesia, in the 5th grade students of MI Maarif NU 01 Sidaurip Binangun Cilacap. Thesis â€ Study Program Islamic Elementary School Teacher Education, Islamic School of The University of Alma Ata, Yogyakarta, 2016. This report aims to review the example non example strategy and to know the students study results on Social Science Subject of the the 5th grade students of MI Maarif NU 01 Sidaurip Binangun Cilacap. This is classroom action research (CAR ). There are the 5th grade students of MI Maarif NU 01 Sidaurip Binangun as the research population which are 27 students ( 16 male and 11 female). The data are collected by observation , interview , tests , and documentation. The data analysis is a qualitative descriptive through several phases namely the data analysis of the learning process, an analysis of the student learning outcome, and making conclusion. The results of this classroom action research shows that the implementation of example non example strategy can improve students learning outcomes in social science subjects especially the history of hindu, buddhist and islam in Indonesia, in the 5th grade students of MI Maarif NU 01 Sidaurip Binangun Cilacap. The Minimum Completeness Criteria (KKM) is 70 and the result was increased. Before the class action implemented (pretest) in the first cycle of the percentage of completeness was 18.5% by number of 5 students and it was increased after class action (post-test) on 55.5% of completeness or 15 students. In the second cycle obtained the pretest percentage of completeness was 44.4% or 12 students and post-test percentage of completeness was 92.6% or 25 students.